2008
DOI: 10.1016/j.ejcts.2008.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative skeletal muscle ischemia contributes to risk of renal dysfunction following thoracoabdominal aortic repair☆☆☆

Abstract: This is the first study to show a relationship between intraoperative leg ischemia and postoperative renal failure. It provides epidemiological evidence that the ischemic leg may be an important contributor to rhabdomyolysis-like renal morbidity after thoracoabdominal aortic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 14 publications
0
39
1
Order By: Relevance
“…In fact, Monsour et al showed that tourniquet-induced limb IR leads to mitochondrial dysfunction in thelung [20]. Miller et al demonstrated that ischemic leg is an important contributor to renal morbidity [21]. The results of several studies suggest that systemic events involving ROS and inflammatory cytokines may play a key role in the remote organ injury induced by limb IR [19,22].…”
Section: Discussionmentioning
confidence: 97%
“…In fact, Monsour et al showed that tourniquet-induced limb IR leads to mitochondrial dysfunction in thelung [20]. Miller et al demonstrated that ischemic leg is an important contributor to renal morbidity [21]. The results of several studies suggest that systemic events involving ROS and inflammatory cytokines may play a key role in the remote organ injury induced by limb IR [19,22].…”
Section: Discussionmentioning
confidence: 97%
“…after successful surgery or endovascular procedures) not only mobilizes the potassium released from damaged cells, but the hyperkalemia is worsened by ischemia-induced acidosis. This is not infrequently encountered in patients having vascular surgery involving large arteries, such as those that require cross-clamping of the aorta [31], and can cause leg ischemia and muscle injury [34]. Ischemia and rhabdomyolysis have also been reported after tourniquet use for hemostasis in the trauma field or for a variety of orthopedic procedures, such as for the hip, ankle and foot [35,36].…”
Section: Potassium Release From Endogenous Sources Damaged Cells 42mentioning
confidence: 99%
“…[1][2][3][4][5] Several techniques have been tried in an attempt to decrease renal complications, including various methods of renal perfusion. [6][7][8][9] Our previous randomized clinical trial 10 compared two renal perfusates: cold crystalloid fluid (lactated Ringer's solution) and isothermic blood from the left heart bypass (LHB) circuit.…”
mentioning
confidence: 99%